DEVELOPMENT OF BASIC ENGLISH GRAMMAR LEARNING MATERIALS USING SOCIAL MEDIA PLATFORM YOUTUBE AT SMK NEGERI 2 RANTAU UTARA - Nasution, Ernida; Muhammad Rusli; Harahap, Anna leli (Program Studi Tadris Bahasa Inggris Sekolah Tinggi Agama Islam Negeri Mandailing Natal, 2025)
This study aims to develop effective and engaging basic English grammar learning materials using the YouTube social media platform for eleventh-grade students at SMK Negeri 2 Rantau Utara. The research employed the ADDIE development model, which includes five phases: Analyze, Design, Develop, Implement, and Evaluate. Data collection techniques included expert validation, student questionnaires, and pre-test and post-test assessments. A total of 20 students participated in the trial implementation. The results of media validation showed a feasibility score of 86%, while content validation reached 93%, indicating that both the media and materials are valid for instructional use. Student feedback revealed high practicality, and learning outcome analysis showed significant improvement, with average post-test scores increasing from 75 to 93.2. These findings suggest that integrating YouTube as a learning platform can enhance students’ understanding of basic English grammar and contribute to a more interactive and student-centered learning environment.